Fuel consumption impacts of auto roof racks. (May 2016) - Chen, Yuche; Meier, Alan
Abstract: The after-market roof rack is one of the most common components attached to a vehicle for carrying over-sized items, such as bicycles and skis. It is important to understand these racks' fuel consumption impacts on both individual vehicles and the national fleet because they are widely used. We estimate the national fuel consumption impacts of roof racks using a bottom-up approach. Our model incorporates real-world data and vehicle stock information to enable assessing fuel consumption impacts for several categories of vehicles, rack configurations, and usage conditions. In addition, the model draws on two new data-gathering techniques, on-line forums and crowd-sourcing. The results show that nationwide, roof racks are responsible for 0.8‰ of light duty vehicle fuel consumption in 2015, corresponding to 100 million gallons of gasoline per year. Sensitivity analyses show that results are most sensitive to the fraction of vehicles with installed roof racks but carrying no equipment. The aerodynamic efficiency of typical roof racks can be greatly improved and reduce individual vehicle fuel consumption; however, government policies to minimize extensive driving with empty racks—if successful—could save more fuel nationally. Highlights: First estimate of national energy impacts of auto roof racks—about 1‰. A bottom-up approach reveals details of the fuel consumption penalty caused by racks. Two novel data collection techniques, on-line forums and crowd-sourcing, improve estimate. Technical and behavioral policies could significantly cut fuel penalties from roof racks.